Spillover effects of targeted subsidies: An assessment of fertilizer and improved seed use in Nigeria - Liverpool-Tasie, Lenis Saweda O.; Salau, Sheu (International Food Policy Research Institute, 2013)
While there is growing evidence of the impact of targeted subsidies on private input demand, as far as we are aware no empirical studies have examined the spillover effects of targeted subsidies for just one input on the use of other complementary inputs with which there is low substitutability. Consequently, this study begins to fill this gap by exploring the effect of increasing access to subsidized fertilizer on farmers’ use of improved seed in Nigeria.